UNDERSTANDING OF RELIGIOUS VALUES AND PSYCHOLOGICAL RESILIENCE AMONG ISLAMIC RELIGIOUS EDUCATION STUDENTS - Aisyah Warasa Fitri; Siti Ubaidah (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the level of understanding of religious values, the level of psychological resilience, and the relationship between the understanding of religious values and psychological resilience among students in the Islamic Education (PAI) Study Program at UIN Sulthan Thaha Saifuddin Jambi. This study was conducted because religious understanding is viewed as one of the key factors that can help students cope with academic pressure and various life challenges in a more adaptive manner. This study employs a quantitative approach using a correlation method. The research sample consisted of 76 sixth-semester students in the PAI program, selected using total sampling. Data were collected using a Likert-scale questionnaire designed based on Glock and Stark’s dimensions of religiosity and Connor and Davidson’s aspects of resilience. Data analysis was performed using descriptive statistics and Spearman’s Rho correlation test because the data were not normally distributed. The results of the study indicate that students’ level of understanding of religious values falls into the high category at 88.46%, while their level of psychological resilience falls into the high category at 76.92%. The correlation test results showed a positive and significant relationship between understanding of religious values and psychological resilience (r = 0.793; p < 0.001 < 0.05). These findings suggest that the higher students’ understanding of religious values, the higher their psychological resilience. The findings of this study reinforce the importance of internalizing religious values in supporting students’ psychological resilience. However, this study is limited to students in the Islamic Education Program at a single university; therefore, the results cannot yet be generalized to a broader population. This study provides empirical evidence regarding the relationship between the understanding of religious values and psychological resilience among PAI students, and reinforces research on the role of religiosity as a psychological resource in coping with academic pressures and daily life.